A Study On The Performances Of Mewma And Mcusum Charts For Skewed Distributions. - B., Michael C. Khoo; M. A. Atta, Abdu.; H, N. Phua (2009)
A multivariate chart, instead of separate univariate charts is used for a joint monitoring of several correlated variables.